Reinterpretation Strengthening Catalog Sharing Using Whatsapp Business As An Online Marketing Media At Pande Besi In Sumberpasir Village - Basid, Abdul (Al-Ijtimā': Jurnal Pengabdian Kepada Masyarakat, 2023)
This service aims to strengthen catalog sharing among micro, small, and medium enterprises (UMKM) in Pande Besi, Sumberpasir Village, using WhatsApp Business as an online marketing medium. The community service assists Pande Besi's UMKM in utilizing WhatsApp Business to promote their products online. The author teaches participants how to create a digital catalog and how to use WhatsApp Business features to facilitate the marketing process.The service is provided through direct training to Pande Besi's UMKM and communication and consultation through a WhatsApp group. This training includes an introduction to WhatsApp Business features, creating a digital catalog using the Canva application, and online marketing strategies through social media. After completing the training, Pande Besi's UMKM were given time to apply the skills learned. As a result, they were able to promote their products online, create digital catalogs, and expand their marketing reach through WhatsApp Business's broadcast and group features. Additionally, Pande Besi's UMKM experienced increased sales and developed new skills in product marketing. By utilizing WhatsApp Business, Pande Besi's UMKM can reach a wider range of consumers and increase their business profits. In conclusion, this community service provides positive benefits for Pande Besi's UMKM. The training helps them develop new skills and use modern technology to market their products. This activity aims to motivate other UMKM to take advantage of social media to promote their products online and improve the welfare of the local community.